Therapeutic efficacy of Artemisia absinthium against Hymenolepis nana: in vitro and in vivo studies in comparison with the anthelmintic praziquantel. Issue 3 (13th June 2017) - Beshay, E.V.N.
Abstract: Hymenolepis nana is a common intestinal tapeworm that affects humans. Drugs are available for the treatment of this infection, including praziquantel (PZQ), nitazoxanide and niclosamide. Although the drug of choice is praziquantel, due to its high cure rates, indicators of the development of PZQ resistance by different parasites have begun to appear over recent decades. Therefore, this study was a trial to find an alternative to PZQ by assessing the activity of the crude aqueous extract of the medicinal herb Artemisia absinthium against H. nana . In vitro, the extract was used against adult worms at concentrations of 1 and 5 mg/ml, in comparison with 1 mg/ml of PZQ. The times of worm paralysis and death were determined. Ultrastructural morphological changes were studied using transmission electron microscopy (TEM). For the in vivo study, infected mice were divided into untreated, PZQ-treated and A. absinthium -treated groups (400 mg/kg and 800 mg/kg). Pre- and post-treatment egg counts per gram of faeces (EPG) were performed; then, the reduction percentages of the EPG and worm burden were calculated. The best results were obtained with praziquantel. Artemisia absinthium induced worm paralysis, death and ultrastructural alterations, such as tegumental damage, lipid accumulation, and destruction of the nephridial canal and the intrauterine eggs, in a dose-dependent manner. Additionally, significant reductions in the EPG and worm burden were recorded in A. absinthium -treated mice. Although the results obtained with A. absinthium were promising and comparable to PZQ, further studies using different extracts, active ingredients and concentrations against different parasites should be conducted.